2017
DOI: 10.5455/medarh.2017.71.396-399
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Abnormalities Found in Patients with Reproductive Problems

Abstract: IntroductionOne of the important causes of male infertility is aberration at the chromosomes.AimThe main purpose of this study was to determine the frequency and types of chromosomal aberration in infertile/sterile men whose samples were analyzed in the Center for Cytogenetics of Faculty of Medicine University of Sarajevo in the last four years.MethodsA total of 353 infertile/sterile men, between the ages of 22-55 years, referred for cytogenetic analysis to the Center for Genetics of Faculty of Medicine during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
2
2
Order By: Relevance
“…Non-pathological structural chromosomal abnormalities were detected in 27/869 (3.11%) control male cases and 39/1160 (3.36%) control female samples. Our results are hard to compare to previously published data due to the types and definitions of chromosomal alterations reported by others [ 11 , 24 , 25 , 26 , 27 , 28 ]. Most of the studies investigating cytogenetic cause of reproductive failure also included heterochromatic polymorphisms among chromosomal aberrations [ 11 , 24 , 25 ], while others did not include these [ 26 , 27 , 28 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Non-pathological structural chromosomal abnormalities were detected in 27/869 (3.11%) control male cases and 39/1160 (3.36%) control female samples. Our results are hard to compare to previously published data due to the types and definitions of chromosomal alterations reported by others [ 11 , 24 , 25 , 26 , 27 , 28 ]. Most of the studies investigating cytogenetic cause of reproductive failure also included heterochromatic polymorphisms among chromosomal aberrations [ 11 , 24 , 25 ], while others did not include these [ 26 , 27 , 28 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are hard to compare to previously published data due to the types and definitions of chromosomal alterations reported by others [ 11 , 24 , 25 , 26 , 27 , 28 ]. Most of the studies investigating cytogenetic cause of reproductive failure also included heterochromatic polymorphisms among chromosomal aberrations [ 11 , 24 , 25 ], while others did not include these [ 26 , 27 , 28 ]. Generally, most reports provided no clarification for the inclusion or exclusion of polymorphic variants in their study.…”
Section: Discussioncontrasting
confidence: 99%
“…KS affects approximately 5 to 10% of infertile men. 10,11 Ferlin et al, 20 observed a similar frequency in azoospermic Klinefelter's individuals and in individuals with severe oligozoospermia the rate was slightly higher (5%). In our study, no individuals in the oligozoospermic group were found to have KS.…”
Section: Discussionmentioning
confidence: 88%
“…This is consistent with the aCGH array data that suggest that this translocation is balanced. Generally, balanced reciprocal translocations do not have a phenotypic effect in carriers, but they can lead to meiotic instability and thus give rise to reproductive problems, usually recurrent pregnancy loss, chromosomally abnormal offspring or infertility [50,51,52], as well as to full-term pregnancies with birth defects [53]. Parental chromosomal rearrangements have been reported in 2–5% of couples with recurrent miscarriages.…”
Section: Discussionmentioning
confidence: 99%